EP1229 Preventing ovarian cancer through early excision of tubes and late ovarian removal (PROTECTOR) study. (1st November 2019) - Gaba, F; Chandrasekaran, D; Menon, U; Evans, G; Singh, N; McCluggage, G; Wilkinson, N; Ganesan, R; Rowlands, G; Bryson, G; Hanson, H; Saridogan, E; et al.
Abstract : Introduction/Background: Aims - To evaluate impact on sexual function, endocrine function, quality-of-life (QoL), health and well-being and determine cost-effectiveness of risk-reducing early-salpingectomy and delayed oophorectomy (RRESDO), as a two-step ovarian cancer (OC) prevention strategy in pre-menopausal women at increased risk of OC. Methodology: Design - Multi-centre, observational cohort controlled trial with three arms: RRESDO; risk-reducing salpingo-oophorectomy (RRSO); controls (no surgery). Inclusion-criteria: Pre-menopausal women; > 30-years; at increased risk of OC (mutation carriers or on basis of a strong family-history; completed their family (for surgical arms). Exclusion-criteria: Post-menopausal women; previous bilateral salpingectomy or bilateral oophorectomy; pregnancy; previous tubal/ovarian/peritoneal malignancy; <12 months post cancer treatment; clinical suspicion of tubal/ovarian cancer at baseline. Recruitment: Through NHS cancer genetics/high-risk familial cancer clinics/general gynaecology clinics/gynaecological oncology clinics/GP surgeries/clinical referrals/supporting charities/self-referral. Primary-outcome: Sexual function. Secondary-outcomes: Endocrine function/menopause; regret/satisfaction; surgical morbidity; QoL/psychological health; number of intraepithelial carcinomas/invasive cancers; utility scores for early-salpingectomy; cost-effectiveness; health and well-being. Consenting individuals for the surgical arms undergo an ultrasound, CA125, FSH and complete questionnaires collecting information on medical history, family-history, QoL, sexual function, cancer worry, psychological well-being and satisfaction/regret. All women undergoing surgery have cytological and histological assessment using a SEE-FIMM protocol, with centralised pathology review. Post-surgery FSH levels are tested and follow-up questionnaires sent at 3 months and annually. Controls have FSH levels checked and complete questionnaires at baseline and annually for three years. Participants from all three arms are invited to take part in semi-structured in-depth interviews. Results: PROTECTOR is open to recruitment across several centres throughout the UK. Conclusion: With growing evidence implicating the role of the fallopian tubes in ovarian carcinogenesis and the detrimental sequelae of surgical menopause in pre-menopausal women following RRSO, PROTECTOR is essential to investigate RRESDO as an alternative risk-reducing strategy in women who do not wish to undergo oophorectomy. Disclosure: RM declares research funding from Barts and The London Charity and Roseetrees Trust for the PROTECTOR Study and is Chief Investigator. RM declares research funding from The Eve Appeal and Cancer Research UK outside this work, as well as an honorarium for grant review from Israel National Institute for Health Policy Research. RM is supported by an NHS Innovation Accelerator (NIA) Fellowship for population testing. FG is an investigator and the study coordinator for the PROTECTOR study. UM has a financial interest in Abcodia Ltd., a company formed to develop academic and commercial development of biomarkers for screening and risk prediction. NS, GM, NW, RG, GR, GB are members of the PROTECTOR central pathology review committee. GE, ES, HH, UM are members of the PROTECTOR trial management committee. MB, RL have nothing to declare.